Memahami Makna Simbol dalam Komunikasi dengan Dayak Jangkang - Sareb Putra, R. Masri (Jurnal Ilmu Komunikasi, 2010)
Abstract: Dayak Jangkang is one of the Dayakâs sub-ethnics that inhabits the Jangkang district, Sanggau regency, West Kalimantan and directly borders with Sarawak, Malaysia. Jangkang Dayak population reaches 45,000. Dayak Jangkang nowadays still maintains and continue the tradition of the ancestors, as reflected in the structure of society, social relations, customs, and culture. Therefore it still maintains and continues the tradition of the Dayak Jangkangâs ancestors in their way of life. Many people, especially those outside Dayak, lack of understanding of their own culture. Therefore, the social conflicts caused by social relations between Dayak Jangkang and migrants (outsiders) are due to the insufficient understanding of the meaning of the symbols.